Hubungan Fungsi Afektif Keluarga dengan Kepercayaan Diri Remaja di SMAN 11 Depok - Asriviananda, Gabriela Rosario (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Mental health issues in Indonesia are on the rise. Self-confidence is a key factor in mental well-being, with families significantly influencing its formation.. This study aimed to analyze the relationship between family affective function and adolescent self-confidence at SMAN 11 Depok. The study adopted a quantitative descriptive correlational design. The research population consisted of 712 students in grades 10 and 11 and the sample comprised 96 respondents selected using the Slovin formula. Data was collected using questionnaires. The results revealed that 28 respondents (59.6%) had high self-confidence and good family affective function. The correlation analysis using the Spearman rho test indicated a p-value of 0.256 (α < 0.05), meaning there was no significant correlation between family affective function and adolescent self-confidence at SMAN 11 Depok. Other factors besides family, such as the school environment and peers, may influence adolescent self-confidence. This research aims to contribute to the development of effective interventions by providing valuable insights for programs that involve families, schools, and the community in preventing low self-confidence in adolecents.